CD70-induced differentiation of proinflammatory Th1/17/22/GM lymphocytes associated with disease progression and immune reconstitution during HIV infection - Xinyue Wang; Yuqing Wei; Zhijiao He; Di Wang; Leidan Zhang; Juan Du; Mengyuan Zhang; Meiqing Jiang; Na Chen; Meiju Deng; Bei Li; Chuan Song; et al. (Emerging Microbes and Infections)
Immune overactivation is a hallmark of chronic HIV infection, which is critical to HIV pathogenesis and disease progression. The imbalance of helper T cell (Th) differentiation and subsequent cytokine dysregulation are generally considered to be the major drivers of excessive activation and inflammatory disorders in HIV infection. However, the accurate factors driving HIV-associated Th changes remained to be established. CD70, which was a costimulatory molecule, was found to increase on CD4+ T cells during HIV infection. Overexpression of CD70 on CD4+ T cells was recently reported to associate with highly pathogenic proinflammatory Th1/Th17 polarization in multiple sclerosis. Thus, the role of CD70 in the imbalance of Th polarization and immune overactivation during HIV infection needs to be investigated. Here, we found that the elevated frequency of CD70 + CD4+ T cells was negatively correlated with CD4 count and positively associated with immune activation in treatment-naïve people living with HIV (PLWH). More importantly, CD70 expression defined a population of proinflammatory Th1/17/22/GM subsets in PLWH. Blocking CD70 decreased the mRNA expression of subset-specific markers during Th1/17/22/GM polarization. Furthermore, we demonstrated that CD70 influenced the differentiation of these Th cells through STAT pathway. Finally, it was revealed that patients with a high baseline level of CD70 on CD4+ T cells exhibited a greater risk of poor immune reconstitution after antiretroviral therapy (ART) than those with low CD70. In general, our data highlighted the role of CD70 in Th1/17/22/GM differentiation during HIV infection and provided evidence for CD70 as a potential biomarker for predicting immune recovery.